Optimalisasi Penerapan Pendidikan Karakter di Sekolah Dasar Berbasis Keterampilan Proses: Sebuah Perspektif Guru PAI - Yayat Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Character education cannot be separated from the world of education. Schools as formal institutions in the education system can be the birthplace of student characters. This brings a moral message that teachers not only educate students by transferring their knowledge, but also pay attention to the development of their character. Education is the key in shaping the character of children from an early age, because the nature of education is not only limited to the transfer of knowledge but also the transfer of values, all of which is done to build the character of the nation's children with noble personalities and overcome children delinquency from various social deviations. This study aims to introduce the optimization of character education through the application of skills-based PAI teaching and learning processes. Students in PAI classes will benefit from this application because students will be involved in the teaching and learning process intellectually, manually, and socially. If the individual character is based on religious values as the main foundation, a strong character will be born and become a strong nation. The main purpose of character education according to Islam is to shape the personality of students so that they have good ethics and a sense of culture and make it happen in everyday life. In addition, they can develop character values such as religious, honest, tolerant, disciplined, creative, independent, fair, curiosity, love to read, and responsibility. Character education that is influenced by PAI-based learning process skills can be the basis for developing optimal student character.